PERAN TEKNOLOGI KEUANGAN DALAM MENINGKATKAN PENGEMBANGAN UMKM PERIKANAN DI PESISIR KALIMANTAN TIMUR - Jainuddin; Yovita, Maria (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
Fisheries Micro, Small, and Medium Enterprises (MSMEs) in the coastal areas of East Kalimantan play a vital role in local economic development, yet they continue to face various challenges such as limited access to financing, low financial literacy, and inadequate technological infrastructure. Financial Technology (fintech) emerges as an innovative solution to address these barriers through digital services such as peer-to-peer lending, digital payments, and automated financial record-keeping applications. This study employs a qualitative approach based on literature review to examine the contribution of fintech in supporting the development of fisheries MSMEs in coastal regions. The findings suggest that fintech can enhance access to finance, improve transaction efficiency, and expand market reach for MSME actors. However, its utilization remains constrained by low digital literacy and limited internet infrastructure in coastal areas. Therefore, collaboration among the government, fintech providers, and educational institutions is essential to strengthen the digital capacity of MSMEs and expand technological infrastructure. This study provides strategic insights into the importance of fintech adoption in promoting inclusive growth and sustainability of fisheries MSMEs in coastal communities.